Lipid disorders in patients of 15 to 64 years old in a policlinic of Rodas municipality. - Manuel Castillo Frías; Ana Teresa Fernández Vidal; Emiliano Diez Martínez; Iván González Solis (Medisur)
Background: Since long time ago clinic medicine established the inexorable progress or development of the human arteriosclerosis, a disease expressed through complications as coronary and cerebrovascular ischemia and obliterant arteriosclerosis of inferior limbs, among others. Objectives: To determine lipid disorders in patients of 15 to 64 years of age of a policlinic in an urban health area. Methods: A transversal cut and descriptive study that included 263 patients to whom the cold test and the cholesterol and triglyceride exams were applied. Results and Conclusions: The risk factors that were more associated with the type of hyperlipoproteinemia were alcoholic consumption, poor nutrition, sedentary habit and overweight. The 26.9% presented hyperlipoproteinemia diagnoses, the 63, 4% of them are masculine and the 50, 7% belonged to the age group of 45 to 54 years old, the one who predominated. The hyperlipoproteinemia type found with more percentage was that of IIb, followed by IIa type and IV type. The non transmissible diseases more associated were arterial hypertension, diabetes mellitus and angina.